Safety behaviour among nurses in a tertiary hospital in Kuala Lumpur - Rohaizah, Mohamad (2017)
The purpose of this study was to determine the relationship between employer’s safety leadership along safety knowledge and safety motivation and safety behaviour among nurses working in the tertiary hospital in Kuala Lumpur. The independent variables were represented by safety leadership namely safety coaching, safety caring and safety controlling along safety knowledge and safety motivation. Safety behaviour which is the dependent variable has been measured by two dimensions namely safety compliance and safety participation. A total of 332 questionnaires were distributed randomly to the nurses in the selected tertiary hospital in Kuala Lumpur during Continuous Nurse Education (CNE) session. The findings of this study revealed that the perceptions of safety leadership with respect to safety controlling along safety knowledge and safety motivation are factors that have significance correlation between safety compliance and safety participation. The findings provide valuable guidance for researchers and practitioners for identifying solutions that can improve safety and health at workplace